Relevant nursing measures for the adverse reactions associated with chimeric antigen receptor T cells (CAR-T) immunotherapy: a systematic review of case reports† - Zhang Xu; Sun Di; Jiang Gui-Chun (Sciendo, 2019)
Cytokine release syndrome (CRS) and tumor lysis syndrome (TLS) that occur after chimeric antigen receptor T (CAR-T) cells are reinfused, which severely affect the survival and prognosis of patients. Although several articles have reported on the care of CAR-T cell immunotherapy, the quality of the study and the effectiveness of holistic nursing interventions have not been systematically reviewed. The purpose of this study was to systematically evaluate the existing holistic nursing interventions of CAR-T cell immunotherapy.